Mulching materials affect growth and yield characters of cucumber (Cucumis sativus cv. Malini) under drip irrigation condition in Chitwan, Nepal - Karki, A.; Sapkota, B.; Bist, P.; Bista, K.; Dutta, J. P.; Marahatta, S.; Shrestha, B. (Journal of Agriculture and Forestry University, 2020)
An experiment was done to evaluate the effect of mulching materials on growth and yield characters of cucumber (var: Malini) under drip irrigation condition during February to May 2018 in Chitwan district, Nepal. The experiment was done by using Randomized Complete Block Design (RCBD). Accordingly, four different mulching materials, viz. silver on black polyethylene mulch, black polyethylene mulch, rice straw mulch, and rice husk mulch were used as treatments. Each treatment was replicated four times. Un-mulched plot served as control. Mulching improved growth and yield characters of cucumber. Plant height and number of leaves were significantly higher (p<0.05) if silver on black polyethylene mulch was used. Similarly, highest number of male (69.50) and female (33.50) flowers per plant were recorded in silver on black polyethylene mulch used. Male flowers were minimum (29.80) in rice husk mulch used treatment whereas female flowers were minimum (10.30) in the control treatment. Sex ratio was the highest (3.43) in control and it was lowest (1.81) for rice husk mulch used treatment. Number of fruit per plant was significantly higher (p<0.05) (15.85) in silver on black polyethylene mulch treatment. Likewise, longest fruit length (18.42 cm) was measured in silver on black polyethylene mulch treatment whereas shortest (15.24 cm) length was measured in control. Yield of silver on black polyethylene mulch and black polyethylene mulch was almost three-folds and two-folds to that of the control, respectively. B: C ratio shows the use of silver on black polyethylene mulch and black polyethylene mulch economically more beneficial in cucumber production with highest benefit. Findings of this experiment thus clearly suggest the benefit of using silver on black polyethylene mulch, as well as black polyethylene mulch in cucumber cultivation compared to the other common mulching materials.